Model Pembelajaran Berorientasi Produksi Dengan Pendekatan Teaching Factory Pada Motivasi Peserta Didik - Helmia, Alifia Farah; Satibi, Ahmad; Cahyadi, Ferry Dwi (Universitas Lampung, 2023)
The dynamic Industry 4.0 requires a workforce that meets industry standards. The quality of education, particularly in vocational high schools, significantly influences the quality of human resources. Vocational high schools are dedicated to preparing students to directly apply their learning in the working world. The aim of this research is to analyze production oriented learning using the teaching factory approach in motivating the production of 'siomay' at SMK 1 Warunggunung. This study employs a quantitative descriptive method and is validated through expert validation using the validity test based on Aiken's V index. Data collection is conducted through questionnaires, interviews, and documentation as supporting evidence. The research findings indicate that, based on the 7 indicators of the teaching factory from the Directorate of Vocational High School Development, the teaching factory approach at SMK 1 Warunggunung falls short of these 7 indicators. The analysis of the teaching factory approach toward student motivation yields an average score of 133.04 and an interval of 109, falling into the high category. This is depicted through descriptive statistical results, revealing that only a portion of students have low learning motivation and there is a need for focused guidance. Keywords: Business World Industrial World, Industry 4.0, Learning Motivation, Teaching Factory,